Lessons learnt from green public procurement in the Norwegian construction sector. Issue 2 (November 2020) - Wiik, Marianne Kjendseth; Flyen, Cecilie; Fufa, Selamawit Mamo; Venås, Christoffer
Abstract: Introduction. Over the next 5 years, Norway shall construct roads, rail tracks and buildings for up to 300 bNOK. Statens vegvesen (SVV), the Norwegian road authority, has calculated that construction, operation and maintenance of Norwegian roads are responsible for 1.5-2m tCO2eq /yr. SVV also found a correlation between cost and emissions and found that every 1MNOK invested leads to ca. 35tCO2eq . When considering the national transport plan (NTP), this equates to 10% of Norway's climate budget. In order to reach climate mitigation goals, public developers have initiated environmental measures in public procurement to reduce GHG emissions. Methods. This paper collects, compares and reviews environmental criteria written into Norwegian public procurement to see which measures are being implemented, how they are being implemented, and to discuss how effective these measures are in cutting GHG emissions. Contracts are sampled from major public developers in the Norwegian construction sector. Results. The results show that public procurers use a range of tools to facilitate for emission reductions. Conclusions. This paper reviews environmental measures in public procurement of Norwegian construction. Lessons learnt may be spread to other countries and the private sector. Grant support. None.